Automation, communication and cybernetics in science and engineering 2009/2010 - Jeschke, Sabina; Isenhardt, Ingrid; Henning, Klaus; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
The book presents a representative selection of all publications published between 01/2009 and 06/2010 in various books, journals and conference proceedings by the researchers of the institute cluster: IMA -Institute of Information Management in Mechanical Engineering ZLW - Center for Learning and Knowledge Management IfU - Institute for Management Cybernetics, Faculty of Mechanical Engineering, RWTH Aachen University The contributions address the cluster's five core research fields: suitable processes for knowledge-and technology-intensive organizations next-generation teaching and learning concepts for universities and the economy cognitive IT-supported processes for heterogeneous and cooperative systems target group-adapted user models for innovation and technology development processes semantic networks and ontologies for complex value chains and virtual environments Innovative fields of application such as cognitive systems, autonomous truck convoys, telemedicine, ontology engineering, knowledge and information management, learning models and technologies, organizational development and management cybernetics are presented. The contributions show the unique potential of the broad and interdisciplinary research approach of the ZLW/IMA and the IfU.
Electronic reproduction.
Keywords: Robotics; Cybernetics; Technological innovations; Science -- Study and teaching; Electronic books